Testing of network security systems through DoS, SQL injection, reverse TCP and social engineering attacks. (3rd December 2019) - Maraj, Arianit; Rogova, Ermir; Jakupi, Genc
Cyber-attacks are happening with an ever-increasing frequency with the goal of gaining access to sensitive information. These attacks can cause huge damage to all kinds of organisations. With web applications becoming a preferred target for attackers through which to try and access sensitive data, it has become of a paramount importance for organisations to implement robust security policies. Measures should be taken to prevent these attacks by testing security systems before attacks happen. The most frequent types of attacks are: SQL injection, DoS, reverse TCP and social engineering. In this paper, we use penetration testing techniques on computer systems and networks. We analyse firewalls and other protective systems and their role through different scenarios. Using penetration testing techniques, we try to find the best solution for protecting sensitive data within the governmental network of Kosovo. We also tackle the issue of social engineering attacks on networks.